(untitled) (Computer systems and information technologies, 2020)
The current state and tendencies and directions of development of equipment and technologies are analyzed. There has been an increase in attention to the characteristics of surfaces and surface layers of parts and elements in various fields, in particular, mechanical engineering, electronics, medicine, etc. One of the effective ways to obtain the formation of surfaces and surface layers with specified high characteristics for compliance with strict requirements for economic efficiency of technological processes is the deposition of particles, including micro- and nanoscale. As a tool for practical solution of the problem, the methodology of simulation modeling in combination with computer technology is proposed. The effectiveness of this approach is demonstrated by examples from various fields of human activity, including computer-aided design systems, mechanical systems calculations, process modeling, systems modeling, urban planning and architecture, optical devices design, electronic devices design, coating applications and properties, medicine, national security, metrology, educational activities. The implemented information system of simulation modeling of the process of particle deposition and surface formation is based on the models of random and dynamic deposition with displacement and without displacement improved taking into account the weight of the particle. Validation and verification of the information system was performed. As directions of further improvement of the implemented system, the implementation of modules for assessing the quality of the obtained surface, in particular, regarding its roughness and porosity, as well as solving the problem of assigning initial parameters and deposition models to obtain a surface with specified quality characteristics.